Sediment transport trend and its influencing factors in coastal bedrock island sea areas-a case study of Chudao island, China - Zhou, Yadi; Wang, Hu; Yan, Yuru (Frontiers in Marine Science, 2023)
Coastal bedrock islands sea areas have a unique natural environment, frequent human activities, and complex sedimentary dynamic processes. In this paper, we select the Chudao Island sea area off the coast of Shandong Peninsula, China, as a typical research area to investigate the sediment transport trends and influencing factors by means of high-precision bathymetric survey, high-density sediment sampling, grain-size trend analysis and hydrodynamic numerical modeling. Results and analysis indicate that the grain size parameters including mean grain-size, sorting coefficient and skewness are zonal distributed, roughly parallel to the isobaths. While the overall sediment transport trend is from island shore to sea, with several convergence centers near the loop centers of bottom flow and at the edge of the agriculture area. The near-bottom flow velocity is primary factor that controlling the significance of sediment transport trend, while the flow decides the general patterns of sediment transport trend and sediment distribution. Submarine topography can either directly transport sediments down its slope, or indirectly affect the direction of sediment transport by constraining the near-bottom flow from shallow to deep waters. Besides the natural factors of bottom flow and submarine topography, human activities represented by aquaculture also affect the sediment transport trend in coastal bedrock island sea areas. First, the increased sedimentation rate caused by organic matters and the diffusion of scallop fragments may cause sediment coarsening. Second, the artificial aquaculture facilities can reduce flow velocity and therefore hinder the initiation, suspension and transport of sediment near the aquaculture areas. Our methods and findings provide high-resolution details to insight into the sediment transport trends to improve the understanding of the modern sediment dynamics in small-scale coastal bedrock island sea areas and provide reference for corresponding engineering and agriculture activities.